Structural reasons for inhibitory effects of pectin on α-amylase enzyme activity and in-vitro digestibility of starch. (May 2021) - Bai, Yeming; Atluri, Sharat; Zhang, Zhongwei; Gidley, Michael J.; Li, Enpeng; Gilbert, Robert G.
Abstract: Excessively rapid postprandial blood glucose increase from digestion of starchy food can lead to health problems, including obesity and type II diabetes. Pectin, a plant polysaccharide dietary fibre, can beneficially affect starch digestion, but the underlying mechanism is not fully understood. Six pectin samples with different molecular structures were used here to study structure-property relationships for the in vitro digestion of starch in the presence of pectin. Three pectin structural features, namely monosaccharide composition, molecular size distribution and degree of esterification, were characterized by high performance liquid chromatography, size-exclusion chromatography and nuclear magnetic resonance, respectively. The effects of pectins on porcine pancreatic α-amylase activity and rheological changes in solutions were also studied, as were the in vitro digestibility of maize starch with and without pectins. The digestibility kinetics were fitted to two models and correlated to other parameters. It was found that (1) all pectin samples comprised mainly homogalacturonan with different degrees of esterification and different molecular sizes, (2) one pectin sample, denoted PGA, with no detectable degree of esterification and small hydrodynamic size, showed a strong amylase inhibitory effect, (3) the viscosity of solutions with pectins were significantly different, and (4) the presence of pectins in digesta did not change the digestion rate of starch, except for PGA, which markedly lowered the extent of starch amylolysis. Finally, the correlation data showed that pectin's degree of esterification plays a key role in pectin's effects on pancreatic amylase activity and on the in vitro digestion of starch. Graphical abstract: Image 1 Highlights: All six pectins are mainly homogalacturonans with diverse esterification degrees. Pectins with various structures showed various effects on starch digestion. Pectins with various structures showed various effects on amylase enzyme activity. One sample, PGA, showed a strong non-competitive amylase inhibitory effect.